Menstrual Hygiene Management Practices and Associated Factors among Secondary School Girls in East Hararghe Zone, Eastern Ethiopia - Hussein Mohammed Gena (Advances in Public Health)
Background. Many adolescent girls in developing countries lack appropriate information, means or materials, and access to the right sanitary facilities to manage menstruation. Hence, they adopted unsafe hygienic practices during menstruation that in turn has a negative impact on their dignity, health, and education. Thus, this study aimed to assess the practices of menstrual hygiene management and associated factors among secondary school girls in East Hararghe Zone. Methods. A school-based cross-sectional study was conducted from April to May 2017 among secondary school girls in East Hararghe Zone, Eastern Ethiopia. A total of 672 girls were selected randomly and interviewed using a structured interviewer-administered questionnaire. Logistic regression analysis was employed to identify predictors of good menstrual hygiene management practices. Result. Overall, 58.3% of the girls had good menstrual hygiene management practices. Around two-thirds (66.1%) of them used commercial sanitary pads as absorbents, 56.4% changed sanitary materials more than three times a day, and 68.3% cleaned their external genitalia daily during their menstruation. During multivariate analysis, living in urban areas (AOR = 2.59, 95% CI: 1.77, 3.80), having moderate (AOR = 2.78, 95% CI: 1.64, 5.28) and good knowledge about menstruation (AOR = 3.87, 95% CI: 2.21, 6.77), and mothers’ secondary and above education (AOR = 1.83, 95% CI: 1.01, 3.30) showed a positively significant association with good menstrual hygiene management practices. Conclusion. In this study, the practice of good menstrual hygiene management of secondary schoolgirls was low. Factors independently influencing menstrual hygiene management practices were girls’ place of residence, knowledge status of menstruation and its hygiene management, and mothers’ educational status. This highlights a need for targeted interventions to raise awareness of school girls especially for rural residents and the public in general to improve the knowledge and practices of menstrual hygiene management.